2015
DOI: 10.1049/iet-com.2014.1249
|View full text |Cite
|
Sign up to set email alerts
|

Near optimal power allocation in two‐way relay systems with physical layer network coding

Abstract: In this study, the authors examine the power allocation (PA) in a two-way relay system, where the relay adopts physical layer network coding based on decode-and-forward protocol. In the PA, the optimisation objective is to minimise the end-to-end symbol error probability (SEP) under a total power constraint. Since the optimal power allocation (OPA) scheme requires numerical methods (for exhaustive search) to find the solution, which might be infeasible for practical systems, the authors propose a near optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…A more comprehensive review on PNC techniques and improvements can be found in [15]. Some other works studied the optimal power allocation for PNC to maximise the system capacity or to minimise BER under sum–power constraints [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…A more comprehensive review on PNC techniques and improvements can be found in [15]. Some other works studied the optimal power allocation for PNC to maximise the system capacity or to minimise BER under sum–power constraints [16, 17].…”
Section: Introductionmentioning
confidence: 99%